A review of the clinical manifestations and laboratory features of patients with plasma cell myeloma: A single centre experience / Salwana Mohd Ali - Salwana, Mohd Ali (2016)
Multiple Myeloma is a clonal plasma cell disorder that varies widely in its clinical course, ranging from relatively indolent forms to frankly aggressive neoplasm. The purpose of this study was to review in detail cases of multiple myeloma diagnosed in University Malaya Medical Centre. we retrospectively reviewed 49 cases of Multiple Myeloma diagnosed within a 7 year period using patient-information system and laboratory information system. Data obtained were patient's demographic, clinical history and diagnosis, laboratory data included complete blood counts, erythrocyte sedimentation rate (ESR), serum calcium, serum albumin, serum creatinine, serum alkaline phosphatase, Bence Jones Protein, serum monoclonal protein, bone marrow findings, cytogenetics and radiological results. Of the 49 patients, 8.2% were younger than 50 years, and 24.5% were 70 years or older. The median age was 66 years. Lumbar back pain was the most common presenting complaint (38.8%) and 12.2% of patients had extramedullary plasmacytoma at diagnosis. Anaemia was present in all patients, hypercalcaemia (calcium level >2.6mmol/L) in 14%, and all 7 patients with positive Bence Jones proteinuria had a creatinine level more than 200μmol/L. lg G kappa was the most common M protein subtype seen in 57.1%. Majority of patient with available FISH results showed normal study. Renal failure and infection were the most common specific cause of death. Key words: multiple myeloma, monoclonal protein, bence jones